Techniques for adaptive prostate radiotherapy. Issue 3 (March 2016) - McVicar, Nevin; Popescu, I. Antoniu; Heath, Emily
Highlights: Current and developing ART techniques for prostate radiotherapy are reviewed. Advantages and disadvantages of supporting in-room imaging technology are discussed. Barrier to clinical implementation of ART is increased demand on clinical resources. Clinical data supporting adoption of ART for prostate cancer is lacking. Abstract: Variations in the position and shape of the prostate make accurate setup and treatment challenging. Adaptive radiation therapy (ART) techniques seek to alter the treatment plan, at one or more points throughout the treatment course, in response to changes in patient anatomy observed between planning and pre-treatment images. This article reviews existing and developing ART techniques for prostate cancer along with an overview of supporting in-room imaging technologies. Challenges to the clinical implementation of adaptive radiotherapy are also discussed.